Education on Recording Students' Personal Health Records to Improve Health Levels at SB Rawang Kuala Lumpur Malaysia - Mitha Amelia Rahmawati; Ardhana Januar Mahardhani; Anik Enikmawati; Dyah Puji Astuti; Flora Ramona Sigit Prakoeswa; Dian Ardifah Iswari; Dadi Rosadi (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
Health is very necessary for every community in various parts of the world. A prosperous society is a big responsibility for the government and also the responsibility of each individual. The recording process must be carried out routinely within one month or every time a patient comes to the student health unit. This community service activity was carried out in the context of an international partnership community service program located at SB Rawang, Malaysia. The objects in the implementation of community service are all students at SB Rawang Selangor Malaysia. Recording of students' personal health records is very necessary considering the benefits include being used as a basis and guide for teachers and UKS managers to find out students' medical history so that if something undesirable happens to students in the future, they can quickly take the right actions on these students. Monitoring the growth and development of students so that the expectation of a good degree of health will be achieved for students